Եղանակի քերականական կարգը գրական արևելահայերենում - Ներսիսյան, Բ.; Ավետիսյան, Ռ. (ՀՀ ԳԱԱ հրատ.)
In contemporary Armenian Studies the problem of the category of Mood in verb, is currently of great interest to the grammarians. It refers to the structures with -ել-ու, -ալ-ու and կ (ր), as well as to the forms with պիտի/պետք է. We think that the structures with -ել-ու, -ալ-ու are not part of the paradigm of the Indicative, as they do not denote an action, but rather present the declined verbal substantive plus substantivized verb and indicate coercion and necessity. Вопросы числа и структуры наклонений глагола по сей день актуальны для армянского языкознания. Речь идет о двух типах конструкций: с -ել-ու, -ալ- ու и կ (ը) и с պիտի/պետք է. На наш взгляд, конструкции с -ել-ու, -ալ-ու не входят в парадигму изъявительного наклонения глагола,так как не выражают реального значения действия, а представляют собой просклоненную форму отглагольного имени с субстантивным глаголом и имеют значение принудительности или необходимости.
Keywords: Գրականություն